CORTICOSTEROID AND LIDOCAIN INJECTION FOR TREATMENT OF HIP OSTEOARTHRITIS : AN UPDATE SYSTEMATIC REVIEW - Hardiyansah, M. Yudhi; Yulanda Putra, Yosie; Auliya, Ahsan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Intraarticular corticosteroid injections (ICSI) can relieve pain in patients with symptomatic osteoarthritis (OA) for weeks. A recent randomized controlled trial showed superior pain improvement following ICSI compared to treatment without injection over a period of 6 months. Atchia et al. compared ICSI to saline-injection and treatment without injection and found ICSI to be the only treatment resulting in significant improvement in both pain and function. The aim: The aim of this study to show about corticosteroid and lidocaine injection for treatment of hip osteoarthritis. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Google Scholar were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search get 7 articles, whereas the results of our search on SagePub get 6 articles, on Google Scholar 1690 articles. Records remove before screening are 1438, so we get 265 articles fos screening. After we screened based on record exclude, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Ultrasound guided intra-articular hip injection of corticosteroid and local anaesthetic, administered with advice and education, is a clinically effective treatment for rapid and sustained symptom response compared with advice and education alone for people with hip osteoarthritis. These findings provide evidence to inform international guidelines and support treatment decision making for policy makers, payers (commissioners), GPs, and clinicians in musculoskeletal services.